WDWXXV : In Light Of 25 Years. - Ayas, Defne; Saelemakers, Samuel; Witte de With - Centre for Contemporary Art, Rotterdam (Rotterdam : Witte de With Center for Contemporary Art, 2015)
Altin, Özlem ; Gartz, Wineke ; Henrot, Camille ; Kruip, Germaine ; Mahony ; Malasauskas, Raimundas ; Taylor, Zin ; Wambacq, Freek ; Zhen, Xu
Witte de With Center for Contemporary Art, Rotterdam, 27 January 2015 - 17 January 2016
kunstcatalogus